Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae) - Lindt, Aare; Hausmann, Axel; Viidalepp, Jaan (Zootaxa, 2018)
The Neotropical geometrine genus Oospila Warren, 1897 includes seventy-nine species and was revised by Cook & Scoble (1995). The genus is distinctive in having a row of raised abdominal crests, which are composed of specialized, erect, metallic shining scales. This paper focuses on the integrative morphological and molecular delimitation of the smallest Oospila species. The wing patterns and genitalia structures of males and females are illustrated. Cook & Scoble (1995) distinguished 13 species groups within Oospila. We discuss the species of the Oospila flavilimes species group, the O. stigma species group and O. miccularia species group below, and separate the O. arpata species complex into a group of its own. Nine new species and two new subspecies are described in this paper: O. cristae sp. n. from Ecuador, O. falcata sp. n. from French Guiana, O. pallidaria boliviensis subsp. n. from Bolivia, and O. loreenae sp. n. from Bolivia (flavilimes species group), O. ehakernae sp. n. from Costa Rica, O. similiplaga bolarpata subsp. n. from Bolivia (arpata species group), O. brehmi sp. n. and O. bifida sp. n. both from Bolivia, O. moseri sp. n. from Brazil, O. absaloni sp. n. and O. pipa sp. n. both from Ecuador (miccularia species group). Oospila similiplaga (Warren) (stat. nov.) is raised here from synonymy with O. arpata (Schaus) and O. imula (Dognin) from synonymy with O. miccularia (Guenée), respectively. Oospila agnetaforslundae nom. nov. is proposed as a replacement name for Oospila marginata Schaus, 1912 (nec Oospila marginata Warren, 1897), raising it to species rank from synonymy of Oospila permagna (Warren, 1909). With this paper, the number of Neotropical Oospila species is raised to 88.